1991
DOI: 10.1177/026565909100700103
|View full text |Cite
|
Sign up to set email alerts
|

Educational and therapeutic approaches used with a child presenting with acquired aphasia with convulsive disorder (Landau-Kleffner Syndrome)

Abstract: This article briefly describes Landau-Kleffner Syndrome and gives the case-history of one child, diagnosed as having this disorder, who presented with severe receptive aphasia. Several of the programmes used in speech therapy and classroom situations are described, including sign language, auditory training, cued articulation, daily diary, and graphic conversation. Some indication of the child's progress is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…So far only a few studies have presented details about speech and language therapy and educational rehabilitation of children with LKS. One exception is the detailed case study by Vance (1991). She used different programmes including sign language.…”
Section: Treatmentmentioning
confidence: 99%
“…So far only a few studies have presented details about speech and language therapy and educational rehabilitation of children with LKS. One exception is the detailed case study by Vance (1991). She used different programmes including sign language.…”
Section: Treatmentmentioning
confidence: 99%
“…-Exploration of reading and mathematics programmes that are best suited to the child's functional level and that will by-pass the difficulty with the auditory channel for processing. -Computer programs with colourful visuals and simple verbal information to assist in learning decoding skills [17,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients and families have reported that sign language has been pivotal in allowing fuller participation of the child in family and social settings, with a concomitant increase in quality-of-life [11]. Finally, cued speech, which involves handshapes made near the mouth to supplement lip-reading, has been suggested as promising based on anecdotal data [15,44].…”
Section: Rehabilitation Issues In Landau-kleffner Syndromementioning
confidence: 99%
“…Case reports document success with using highly visual strategies in the classroom, as processing of non-verbal information is unimpaired in LKS [15]. For example, picture schedules, colour coding to support letter and sound identification while reading, storyboards for instructions and graphic conversation have been reported to be helpful to students [15,41,44]. Computer programs are suggested to support reading comprehension [41].…”
Section: Rehabilitation Issues In Landau-kleffner Syndromementioning
confidence: 99%